Flipped Learning: Asynchronous and Synchronous Models in Online Class to Improve the Learning Outcomes - St Hartina; Ermawati Ermawati; Syahrir Syahrir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Flipped learning is a strategy for assisting the online learning process. This study attempts to adopt it in an online class using a quasi-experimental design with a post-test-only control to examine its effects on student learning outcomes. Data was obtained from reading tests administered to students enrolled in the fifth semester of the English Education Department at IAIN (State Islamic Institute) of Palopo. This study discovered at least three findings suggesting that flipped learning improves student learning outcomes significantly. First, students' mean score in the experimental class is higher (x = 70.11) than in the control class (x = 58.70). Second, the significance value (Sig. 2-tailed) is 0.000<0.05, indicating a significant effect of the experimental class implementation of flipped learning. Third, the effect size is 1.106 with an influence percentage of 86 percent which categorized has a large effect based on Cohen’s criteria.  The author proposes utilizing a flipped learning technique as a substitute for online learning in light of the findings.